Screening of french bean (Phaseolus vulgaris L.) genotypes for high yield potential - Noor, F; Hossain, F; Ara, U (Bangladesh Journal of Scientific and Industrial Research, 2015)
Eleven genotypes of french bean (Phaseolus vulgaris L.) were screened to select a suitable one which could provide optimum yield of fresh pod, dry seed and biochemical parameters. The maximum seed yield in french bean was found in case of genotype BB-9 (2.96 t/ha) and BARI bush bean -1 (2.95 t/ha), while that of minimum was found in BB-11(1.64 t/ha). However, maximum fresh pod yield (14.25 t/ha) was found for BARI bush bean -1, followed by BARI bush bean -2 (13.23t/ha). BARI bush bean -1 required the minimum time of 88.33 days while BB-3 the maximum of 110.00 days to attain 90% pods maturity. The highest number of diseased plants were observed in BB- 5 (30.33%) and the lowest were in BARI bush bean -1 (7.33%). No significant difference (P< 0.05) in maximum protein content among the studied genotypes was observed, for example BB-15 (21.60%) and BARI bush bean -1 (21.57%). Maximum crude fiber (5.53%) was obtained from BARI bush bean -1, followed by BB-6 (5.50%), BB-20 (5.50%) and BB-5 (5.47%), which all were statistically similar. Among all the genotypes, BARI bush bean -1 showed highest yield and superior quality of french bean. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22625 Bangladesh J. Sci. Ind. Res. 49(4), 227-232, 2014